Salmonella quantification (SalQuant®) utilizing BAX® system for pork primary production samples and exploring the use of Probicon L28 and BIOPLUS® 2B as direct-fed microbials to reduce Salmonella and Shiga toxin-producing Escherichia coli in market pigs - Bai, Jimeng (Kansas State University, 2023)
Salmonella is a common pathogen in pigs, and pork has been associated with causing salmonellosis in humans. Because pigs infected with pathogens can transport the pathogens to the abattoir and contaminate pork products, the identification and validation of a rapid and effective method for the detection and quantification of Salmonella in pre-harvest and harvest samples would benefit the pork industry. Because Salmonella is commonly found in the intestines and lymph nodes of pigs, as well as farm environments, it is possible to quantify Salmonella using pre-harvest and harvest samples. The first study validated SalQuant® System as a polymerase chain reaction (PCR) assay for the quantification of Salmonella in boot covers, ropes, spleens, and pig feces. Samples negative for Salmonella were inoculated with Salmonella Typhimurium 14028 strains at 0 to 4 or 0 to 8 log CFU/g and samples were subjected to the BAX® Real-Time Salmonella assay after 0 (5 to 8 log CFU/g samples only), 6, 8, and 10 hours of incubation at 42ºC. Three biological replicates and 5 technical replicates were completed for each sample type, and one biological replicate was also enumerated using the most probable number (MPN) technique as a comparison. After data collection, a linear fit equation was established for all incubation times, with R² > 0.80, log RMSE < 0.60 used as the threshold for identifying the incubation time that is most effective for quantifying Salmonella. A paired t-test compared the Salmonella concentrations generated by MPN and SalQuant® for one biological replication, and the two methods were not significantly different (P>0.05) for all sample types except spleens (P=0.0246). Shiga toxin-producing Escherichia coli (STEC) is another pathogen that can be found in pigs and in their farm environments. Identifying effective pre-harvest interventions can reduce pathogens in market pigs to reduce the burden of pathogens entering the abattoir. Many studies have demonstrated that Lactobacillus is an effective pre-harvest intervention in cattle, particularly in controlling Escherichia coli O157:H7. Lactobacillus salivarius L28 (Probicon L28) is a patented probiotic that can be given to animals as a pre-harvest food safety intervention to reduce pathogens. BIOPLUS® 2B is a probiotic comprised of Bacillus subtilis and Bacillus licheniformis. It is commonly used in the pig industry to establish gastrointestinal microbiota and promote animal health. The purpose of the second study was to investigate BIOPLUS® 2B and Probicon L28 as pre-harvest interventions to reduce Salmonella and Shiga toxin-producing E. coli in market pigs. Two groups of market pigs (N=294 pigs in group 1; N=356 in group 2, initial weight = 116.2 lb) were enrolled in the study. A total of 36 pens were used for each group of pigs and pigs were assigned at random to pen. Each pen was assigned to one of three treatments, with a total of 12 pens per treatment: a control treatment consisting of a standard corn-soybean meal (SBM) finishing diet (no probiotic), a standard corn-SBM finishing diet supplemented with Probicon L28 (target concentration of 1.0×10⁶ CFU/head/day) through water lines using a water medication system, a standard corn-SBM finishing diet supplemented with BIOPLUS® 2B at a target concentration of 3.0×10⁹ CFU/head/day. Each group of pigs was sampled at three stages during the feeding period (arrival/baseline, halfway/6 weeks and prior to loadout/13 weeks), and at each stage the following samples were collected: feces collected from four pigs at random in each pen, two boot covers per pen, and one rope sample per pen. Market pigs were followed to the abattoir and superficial inguinal lymph nodes were collected from each pig. The BAX® System was used to detect Salmonella, E. coli O157:H7, and Shiga toxin-producing E. coli (stx, eae genes, serogroups O26, O121, O45, O103 and O145). In this study, Salmonella prevalence was very low at less than 3% for all sample types collected from group 1 and 2 pigs. Dietary supplementation of BIOPLUS® 2B and Probicon L28 in finishing pigs had no effect (P>0.05) on the prevalence of STEC (stx and eae genes) or serogroups O26, O121, O45, O103 and O145 in pig feces, boot covers, and ropes prior to loadout, or lymph nodes collected at the abattoir.
Keywords: Salmonella; STEC; Swine; SalQuant®; BAX®; Probiotic